Peran TBM Bilik Urang Dalam Pembelajaran Literasi Dasar Anak Pra Sekolah - Mahira Mujahida Ani Mufti; Anita Anita; Evi Afiati (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2022)
As a provision during the school period, it is important to introduce literacy to pre-school children. Community Reading Park (TBM) is one of the facilities that facilitate pre-school children in recognizing literacy. In this regard, it is important to explore how TBM introduces literacy to pre-school children. For this reason, this study discusses the role of the Bilik Urang community reading garden in introducing basic literacy to early childhood children in Cigadung Village, the majority of whom have low incomes. This study used a qualitative approach where data collection techniques were carried out through interviews, observations, and literature reviews. This study aims to describe the role of TBM Bilik Urang in introducing basic literacy to pre-school children and how volunteers manage the Bilik Urang Community Reading Park and implement basic literacy teaching strategies. The results of this study indicate that 1) the existence of TBM Bilik Urang helps introduce literacy to pre-school children, especially those from low-income families, 2) TBM Bilik Urang volunteers have a role in introducing literacy to children through planned strategies and activities.